The role of clinical judgment in integration of indicators of outcome in psychotherapy research. Issue 3 (12th March 2015) - Yasky, Jaime; King, Robert; O'Brien, Tom
Abstract Background Evaluation of psychotherapy impact and effect has advanced substantially in the last half century. The development of reliable standardised measures has been especially important. However, several issues remain controversial. One such issue is the extent to which standardised measures adequately capture change and their integration with normal clinical practice. A second is how to deal with the not uncommon situation where one outcome measure indicates change and another does not. Finally, researchers are often confronted with cases where standardised measures are used, but some participants quit therapy without completing them. Aim In this study, we present and discuss an outcome assessment method developed in the context of a naturalistic, mixed‐methods study of 22 treatments of psychosomatic patients. Methodology This multimodal, multi‐informant method involved a thorough and individualised analysis of transcripts, questionnaires and other clinical data, the consideration of patient and therapist's opinions about outcome, and the use of clinical judgment to integrate different indicators and classify outcome, with the aid of two auditors reviewing the process. Findings Eight cases improved, six deteriorated, and eight did not change. Three case vignettes illustrate the application of the method, and some possible sources of bias of patient and therapist's opinion about outcome are identified. Implications Clinical judgment can help integrate results from standardised measures and other data sources into outcome assessment normally practised by clinicians. This method, besides its high cost in time and resources, can also be useful in research to rescue outcome assessment when collection of outcome measures fails.